2021
DOI: 10.2147/ijn.s289096
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Halofuginone Hydrobromide in TPGS Polymeric Micelles Enhances Efficacy Against Triple-Negative Breast Cancer Cells

Abstract: Background Halofuginone hydrobromide (HF) is a synthetic analogue of the naturally occurring quinazolinone alkaloid febrifugine, which has potential therapeutic effects against breast cancer, however, its poor water solubility greatly limits its pharmaceutical application. D-α-tocopherol polyethylene glycol 1000 succinate (TPGS) is a water-soluble derivative of vitamin E, which can self-assemble to form polymeric micelles (PMs) for encapsulating insoluble anti-tumor drugs, thereby effectively enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…The optimal formulation of HTPM had an HD of 17.8 ± 0.5 nm ( Figure 2A ), which contributes to the penetration of and/or interaction with dense microvilli (microvillus diameter ∼100 nm). 17 In addition, the PDI of HTPM was 0.212 ± 0.1, suggesting its high homogeneity. A recent investigation has shown that the ZP of drug-free TPGS polymer micelles was negative.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The optimal formulation of HTPM had an HD of 17.8 ± 0.5 nm ( Figure 2A ), which contributes to the penetration of and/or interaction with dense microvilli (microvillus diameter ∼100 nm). 17 In addition, the PDI of HTPM was 0.212 ± 0.1, suggesting its high homogeneity. A recent investigation has shown that the ZP of drug-free TPGS polymer micelles was negative.…”
Section: Resultsmentioning
confidence: 96%
“… 27 Herein, HTPM have been successfully prepared by the thin-film hydration method ( Figure 1 ), as reported previously. 17 For oral delivery, the particle size and surface charge of the self-assembled micelles appear to be the most important parameters, which greatly influence the transport route of micelles through the intestinal epithelium membrane and determine their stability. 40 Thus, the HD, PDI, and ZP were determined by DLS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also exhibited enhanced tumor growth inhibition (68.17%) in comparison to free drugs. Hence it was concluded that polymeric micelles hold significant clinical potential for the treatment of TNBC [ 258 ].…”
Section: Nanotechnology: Cavalry For Tnbc Therapymentioning
confidence: 99%